Highly Branched Sn-Doped ZnO Nanostructures for Sunlight Driven Photocatalytic Reactions. (11th December 2014) - Liu, Yangyang; Chen, Xiaodong; Xu, Ying; Zhang, Quanhua; Wang, Xianying
Abstract : Ultralong, highly branched Sn-doped zinc oxide (ZnO) nanostructures were fabricated using a simple substrate-free chemical vapor deposition (CVD) method. The nanostructures exhibited efficient photocatalytic activities in degradation of methylene blue (MB) under natural sunlight. 100% of MB with the concentration of 10 mg/L could be completely removed within 36 minutes. Possible reasons for the enhanced photocatalytic effect were analyzed.